Metal-coated hollow glass microsphere, and preparation method and application thereof
Patent Information
- Application Number
- CN202511068971.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-31
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-07-31
AI Technical Summary
[0004]上述采用增大套管钢级与壁厚的方法无法有效抵抗地层滑移产生的剪切力,且可能因应力集中加剧变形风险;而采用含有空心材料的固井水泥应对套管变形,其密度不足难以满足常规固井要求,且微珠吸收变形能力有限,无法有效缓解套管与地层间的位移差异
[0054](1)本发明提供的金属镀层空心玻璃微珠,将空心玻璃微珠与锡锌合金镀层相结合,形成轻质内核与高密度镀层的复合结构,在压裂过程中,裂缝被压裂流体激活后滑移,破碎水泥石和金属镀层空心玻璃微珠,金属镀层空心玻璃微珠破碎后提供地层滑移空间,从而减少了套管变形;另外,通过外层锡锌合金镀层将空心玻璃微珠整体密度提升至1.6-2.1g/cm3,远超常规空心微珠的密度,与常规固井水泥浆密度1.8-2.1g/cm3完全匹配,解决了传统空心微珠因密度过低导致的固井质量下降的问题。本发明提供的金属镀层空心玻璃微珠还具有良好的力学性能与耐腐蚀性,能够满足极端环境下的应用需求。
Smart Images

Figure CN121005526B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of shale oil and gas cementing technology, specifically to a metal-coated hollow glass microsphere, its preparation method, and its application. Background Technology
[0002] In shale oil and gas hydraulic fracturing development, casing deformation has become a core bottleneck restricting efficient development. Due to the development of bedding, natural fractures, and faults in shale reservoirs, fracturing fluid penetrates through the contact surfaces of fractures, bedding planes, or cement sheaths with the formation, reducing the friction coefficient of the fracture surface and triggering the slippage of the developed fractures. This, in turn, applies shear loads to the casing, leading to plastic deformation or localized stress concentration. Field data shows that the shear displacement caused by formation slippage is typically 15-25 mm. Although it may not shear the casing, it is sufficient to cause problems such as difficulty in tool insertion and abandonment of fracturing sections, resulting in low single-well production and the inability to operate some wells, thus reducing shale oil and gas production.
[0003] Currently, researchers have proposed using casing with higher steel grades and thicker walls to combat deformation caused by formation slippage. For example, CN214464059U discloses a cementing tool that enhances the shear performance of casing in formation slippage sections. This tool includes a high-steel-grade casing installed within a wellbore in a formation fault. The outer wall of the casing within the wellbore is filled with a flexible cement sheath or a conventional cement sheath between itself and the formation. Conventional cement sheaths are also filled between the upper and lower outer walls of the casing and the formation. An expansion tube is installed between the cement sheath within the wellbore and the formation, and a corrugated pipe is installed between the casing and the cement sheath. Other researchers have proposed using cementing materials containing hollow materials to address casing deformation. For example, CN115286306A discloses a cement slurry for inhibiting casing deformation and its preparation method. The cement slurry for inhibiting casing deformation is obtained by mixing the following raw materials in parts by mass: based on 100 parts by mass of silicate cement, the amounts of each component are: 25-30.0 parts of silica powder, 10.0-50.0 parts of strain agent, 0.5-4.0 parts of microsilica, 2.0-4.0 parts of expansion agent, 0.8-1.4 parts of dispersant, 1.4-2.1 parts of fluid loss reducing agent, 0.1-0.8 parts of retarder, 0.2-0.25 parts of defoamer, and 55-85 parts of water.
[0004] The methods mentioned above, such as increasing the casing steel grade and wall thickness, cannot effectively resist the shear force generated by formation slippage, and may exacerbate the risk of deformation due to stress concentration. On the other hand, using cementing cement containing hollow materials to deal with casing deformation is insufficient in density to meet the requirements of conventional cementing, and the deformation absorption capacity of microspheres is limited, which cannot effectively alleviate the displacement difference between the casing and the formation.
[0005] In summary, there is an urgent need to develop a technical solution that can meet the requirements of cement slurry density, facilitate construction, and effectively absorb casing deformation. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the present invention aims to provide a metal-coated hollow glass microsphere, its preparation method, and its application. The metal-coated hollow glass microsphere can effectively absorb casing deformation and displacement caused by crack sliding, while meeting the density requirements of cementing slurry, thereby improving the overall efficiency of shale oil and gas development.
[0007] To achieve this objective, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a metal-coated hollow glass microsphere, wherein the metal-coated hollow glass microsphere comprises soda lime borosilicate hollow glass microspheres and a tin-zinc alloy coating coated on its surface; the density of the metal-coated hollow glass microsphere is 1.6-2.1 g / cm³. 3 .
[0009] The density of the metal-coated hollow glass microspheres is 1.6-2.1 g / cm³. 3 For example, it could be 1.6 g / cm³ 3 1.7g / cm 3 1.8g / cm 3 1.9g / cm 3 2g / cm 3 Or 2.1g / cm 3 However, this does not limit the listed values; other unlisted values within the range are also applicable.
[0010] The metal-coated hollow glass microspheres provided by this invention combine hollow glass microspheres with a tin-zinc alloy coating to form a composite structure of a lightweight core and a high-density coating. During fracturing, the fracture is activated by the fracturing fluid and then slides, breaking up the cement stone and the metal-coated hollow glass microspheres. The broken metal-coated hollow glass microspheres provide space for formation slippage, thereby reducing casing deformation. In addition, the outer tin-zinc alloy coating increases the overall density of the hollow glass microspheres to 1.6-2.1 g / cm³. 3 Its density far exceeds that of conventional hollow microspheres, compared to the density of conventional well cement slurry (1.8-2.1 g / cm³). 3 The perfect match solves the problem of reduced cementing quality caused by the low density of traditional hollow microspheres. The metal-coated hollow glass microspheres provided by this invention also possess excellent mechanical properties and corrosion resistance, meeting the application requirements in extreme environments.
[0011] Preferably, the diameter of the soda lime borosilicate hollow glass microspheres is in the range of 100-250 μm, and the average diameter can be, for example, 100 μm, 110 μm, 120 μm, 150 μm, 200 μm, 240 μm or 250 μm, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0012] Preferably, the wall thickness of the soda lime borosilicate hollow glass microspheres is 1-2 μm, and the average wall thickness can be, for example, 1 μm, 1.2 μm, 1.5 μm, 1.8 μm or 2 μm, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0013] Preferably, the density of the soda lime borosilicate hollow glass microspheres is 0.12-0.8 g / cm³. 3 The average density could be, for example, 0.12 g / cm³. 3 0.2g / cm 3 0.4g / cm 3 0.6g / cm 3 or 0.8g / cm 3 However, this does not limit the listed values; other unlisted values within the range are also applicable.
[0014] The soda lime borosilicate hollow glass microspheres are characterized by high lightness, good thermal insulation, good dispersibility, and good flowability, and can be well dispersed in cementing slurry. It should be noted that the size of the soda lime borosilicate hollow glass microspheres can be adaptively adjusted according to the complexity of the fracture and the geological conditions of the block.
[0015] It should be noted that the ratio of zinc to tin in the tin-zinc alloy coating described in this invention can be adjusted adaptively according to the actual application scenario, which will not be elaborated upon in this invention.
[0016] The zinc content is 13-17 wt%, for example, it can be 13 wt%, 14 wt%, 15 wt%, 16 wt% or 17 wt%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0017] Preferably, the density of the tin-zinc alloy coating is 7.1-7.5 g / cm³. 3 For example, it could be 7.1 g / cm³ 3 7.2g / cm 3 7.3g / cm 3 7.4g / cm 3 Or 7.5g / cm 3 However, this does not limit the listed values; other unlisted values within the range are also applicable.
[0018] Preferably, the thickness of the tin-zinc alloy coating is 10-20 μm, for example, it can be 10 μm, 12 μm, 15 μm, 18 μm or 20 μm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0019] The tin-zinc alloy coating has good corrosion resistance and high temperature resistance, as well as high density and certain pressure bearing capacity. Currently, the shale oil and gas extraction depth is 3000-4500m, the bottom pressure is close to 100MPa, and the well temperature is about 130-150℃. The melting point of the tin-zinc alloy coating is ≥220℃, which can adapt to the extreme environment at the bottom of the well and meet the needs of deep wells.
[0020] In a second aspect, the present invention provides a method for preparing metal-coated hollow glass microspheres as described in the first aspect, the method comprising the following steps:
[0021] Surface-treated soda lime borosilicate hollow glass microspheres are immersed in an electrolyte for electroplating to obtain electroplated glass microspheres; the obtained electroplated glass microspheres are then passivated to obtain the metal-coated hollow glass microspheres.
[0022] The method for preparing metal-coated hollow glass microspheres provided by this invention involves electroplating with an electrolyte of a specific formulation. The electrolyte contains metal ions, which are reduced to metal and deposited on the hollow glass microspheres by the action of an electric current, forming a metal coating on the surface. Passivation treatment of the electroplated glass microspheres can ensure the corrosion resistance, sulfur resistance, compressive strength, and ductility of the metal coating under high temperature and high pressure well conditions.
[0023] Preferably, the surface treatment includes acid washing and / or alkaline washing.
[0024] The purpose of the surface treatment is to remove oxides and other impurities from the surface of the hollow glass microspheres.
[0025] Preferably, the reagents used for pickling include hydrochloric acid and / or nitric acid.
[0026] Preferably, the reagents used for alkaline washing include sodium hydroxide and / or sodium carbonate.
[0027] Preferably, the electrolyte comprises, by weight fraction: 10-15 parts stannous sulfate, 10-15 parts zinc sulfate, 35-40 parts main complexing agent, 20-25 parts auxiliary complexing agent, 10-15 parts pH adjuster, 10-15 parts stabilizer, and 5-10 parts brightener.
[0028] Preferably, the primary complexing agent comprises citric acid.
[0029] This invention utilizes citrate as the main complexing agent, stannous sulfate and zinc sulfate to provide tin ions and zinc ions respectively, and uses auxiliary complexing agents to enhance the stability of metal ions and improve the dispersion ability of the plating solution. Stabilizers are added to prevent metal ions from hydrolyzing, oxidizing or undergoing other side reactions, thus maintaining the long-term stability of the plating solution.
[0030] The weight fraction of stannous sulfate in the electrolyte is 10-15 parts, for example, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts, but not limited to the listed values. Other unlisted values within the range are also applicable.
[0031] The zinc sulfate in the electrolyte has a weight fraction of 10-15 parts, for example, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0032] The weight fraction of the main complexing agent in the electrolyte is 35-40 parts, for example, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts or 40 parts, but not limited to the listed values. Other unlisted values within the range are also applicable.
[0033] The weight fraction of the auxiliary complexing agent in the electrolyte is 20-25 parts, for example, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts or 25 parts, but not limited to the listed values. Other unlisted values within the range are also applicable.
[0034] The weight fraction of the pH adjuster in the electrolyte is 10-15 parts, for example, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts, but not limited to the listed values. Other unlisted values within the range are also applicable.
[0035] The weight fraction of the stabilizer in the electrolyte is 10-15 parts, for example, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts, but not limited to the listed values. Other unlisted values within the range are also applicable.
[0036] The brightener in the electrolyte has a weight fraction of 5-10 parts, for example, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0037] Preferably, the auxiliary complexing agent comprises: 5-10 parts tartaric acid and 15-20 parts ammonium salt.
[0038] The weight fraction of tartaric acid in the auxiliary complexing agent is 5-10 parts, for example, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts, but not limited to the listed values. Other unlisted values within the range are also applicable.
[0039] The weight fraction of ammonium salt in the auxiliary complexing agent is 15-20 parts, for example, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts, but not limited to the listed values. Other unlisted values within the range are also applicable.
[0040] Preferably, the ammonium salt includes at least one of ammonium sulfate, ammonium nitrate, or ammonium chloride.
[0041] Preferably, the pH adjuster includes ammonia.
[0042] Preferably, the stabilizer includes any one of malic acid, glycolic acid, lactic acid, glycolic acid, and their salts.
[0043] Preferably, the brightener comprises at least one of sodium dodecyl sulfate, formaldehyde, or o-toluidine condensate.
[0044] Preferably, the current density of the electroplating treatment is 1-2.4 A / dm³. 2 For example, it could be 1A / dm 2 1.2A / dm 2 1.5A / dm 2 2A / dm 2 Or 2.4A / dm 2 However, this does not limit the listed values; other unlisted values within the range are also applicable.
[0045] Preferably, the passivating agent used in the passivation treatment comprises a mixed aqueous solution of nitric acid and sodium dichromate, wherein the mass concentration of nitric acid is 20-30% and the mass concentration of sodium dichromate is 1-2%.
[0046] The mass concentration of nitric acid in the mixed aqueous solution is 20-30%, for example, it can be 20%, 22%, 25%, 28% or 30%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0047] The mass concentration of sodium dichromate in the mixed aqueous solution is 1-2%, for example, it can be 1%, 1.2%, 1.5%, 1.8% or 2%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0048] Preferably, the passivation treatment is performed at a temperature of 50-70°C for 30-90 minutes.
[0049] The passivation treatment temperature is 50-70℃, for example, it can be 50℃, 55℃, 60℃, 65℃ or 70℃, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0050] The passivation treatment time is 30-90 minutes, for example, it can be 30 minutes, 40 minutes, 50 minutes, 60 minutes, 70 minutes, 80 minutes or 90 minutes, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0051] Thirdly, the present invention provides an application of metal-coated hollow glass microspheres as described in the first aspect, wherein the metal-coated hollow glass microspheres are used as an additive for preventing the cement slurry from turning into a mold.
[0052] The metal-coated hollow glass microspheres are introduced into the wellbore along with the cement slurry during the cementing process. After the cement slurry sets, they form spaces that absorb the displacement when fractures are activated and slip due to hydraulic fracturing fluid. This protects the casing from formation shear and ensures the smooth insertion of fracturing tools, thereby increasing single-well production. The amount of metal-coated hollow glass microspheres added can also be controlled according to the severity of the fracture on site.
[0053] Compared with the prior art, the present invention has the following beneficial effects:
[0054] (1) The metal-coated hollow glass microspheres provided by this invention combine hollow glass microspheres with a tin-zinc alloy coating to form a composite structure of a lightweight core and a high-density coating. During fracturing, the fracture is activated by the fracturing fluid and then slides, breaking the cement stone and the metal-coated hollow glass microspheres. The broken metal-coated hollow glass microspheres provide space for formation slippage, thereby reducing casing deformation. In addition, the overall density of the hollow glass microspheres is increased to 1.6-2.1 g / cm³ through the outer tin-zinc alloy coating. 3 Its density far exceeds that of conventional hollow microspheres, compared to the density of conventional well cement slurry (1.8-2.1 g / cm³). 3 The perfect match solves the problem of reduced cementing quality caused by the low density of traditional hollow microspheres. The metal-coated hollow glass microspheres provided by this invention also possess excellent mechanical properties and corrosion resistance, meeting the application requirements in extreme environments.
[0055] (2) The method for preparing metal-coated hollow glass microspheres provided by the present invention uses an electrolyte with a specific formula for electroplating treatment. The electrolyte contains metal ions, and the metal ions are reduced to metal and deposited on the hollow glass microspheres by the action of current, forming a metal coating on the surface. Passivation treatment of the electroplated glass microspheres can ensure the corrosion resistance, sulfur resistance, compressive strength and ductility of the metal coating under high temperature and high pressure well conditions. Attached Figure Description
[0056] Figure 1 This is an SEM image of the metal-coated hollow glass microspheres provided in Embodiment 1 of the present invention. Detailed Implementation
[0057] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention.
[0058] Example 1
[0059] This embodiment provides a metal-coated hollow glass microsphere, which includes soda lime borosilicate hollow glass microspheres and a tin-zinc alloy coating on their surface. The SEM image of the metal-coated hollow glass microsphere is shown below. Figure 1 As shown in the figure, the mixture is composed of cement slurry and metal-coated hollow glass microspheres, the density of which is 1.8 g / cm³. 3 .
[0060] The soda lime borosilicate hollow glass microspheres have an average diameter of 200 μm, an average wall thickness of 1.5 μm, and an average density of 0.4 g / cm³. 3 The density of the tin-zinc alloy coating is 7.3 g / cm³. 3 The thickness is 15μm.
[0061] The method for preparing the metal-coated hollow glass microspheres includes the following steps:
[0062] Hollow glass microspheres of soda lime borosilicate, which had been pickled with hydrochloric acid and alkali-washed with sodium hydroxide, were immersed in an electrolyte for electroplating treatment at a current density of 1.5 A / dm³. 2 Electroplated glass microspheres were obtained; the obtained electroplated glass microspheres were passivated at 60°C for 60 min using a mixed aqueous solution of nitric acid and sodium dichromate, wherein the mass concentration of nitric acid in the mixed aqueous solution was 25% and the mass concentration of sodium dichromate was 1.5%, thus obtaining the metal-coated hollow glass microspheres.
[0063] The electrolyte comprises, by weight fraction: 12 parts stannous sulfate, 13 parts zinc sulfate, 38 parts citric acid, 7 parts tartaric acid, 16 parts ammonium sulfate, 12 parts ammonia, 13 parts malic acid, and 8 parts sodium dodecyl sulfate.
[0064] Example 2
[0065] This embodiment provides a metal-coated hollow glass microsphere, comprising soda lime borosilicate hollow glass microspheres and a tin-zinc alloy coating on their surface, wherein the density of the metal-coated hollow glass microsphere is 1.7 g / cm³. 3 .
[0066] The soda lime borosilicate hollow glass microspheres have an average diameter of 100 μm, an average wall thickness of 1 μm, and an average density of 0.12 g / cm³. 3 The density of the tin-zinc alloy coating is 7.1 g / cm³. 3 The thickness is 10μm.
[0067] The method for preparing the metal-coated hollow glass microspheres includes the following steps:
[0068] Soda lime borosilicate hollow glass microspheres, which had been acid-washed with hydrochloric acid and alkaline-washed with sodium hydroxide, were immersed in an electrolyte for electroplating treatment at a current density of 1 A / dm³. 2 Electroplated glass microspheres were obtained; the obtained electroplated glass microspheres were passivated at 50°C for 90 min using a mixed aqueous solution of nitric acid and sodium dichromate, wherein the mass concentration of nitric acid in the mixed aqueous solution was 20% and the mass concentration of sodium dichromate was 1%, thus obtaining the metal-coated hollow glass microspheres.
[0069] The electrolyte comprises, by weight fraction: 10 parts stannous sulfate, 10 parts zinc sulfate, 35 parts citric acid, 5 parts tartaric acid, 15 parts ammonium nitrate, 10 parts ammonia, 10 parts glycolic acid, and 5 parts formaldehyde.
[0070] Example 3
[0071] This embodiment provides a metal-coated hollow glass microsphere, comprising soda lime borosilicate hollow glass microspheres and a tin-zinc alloy coating on their surface, wherein the density of the metal-coated hollow glass microsphere is 2 g / cm³. 3 .
[0072] The soda lime borosilicate hollow glass microspheres have an average diameter of 250 μm, a wall thickness of 2 μm, and a density of 0.8 g / cm³. 3 The density of the tin-zinc alloy coating is 7.5 g / cm³. 3 The thickness is 20μm.
[0073] The method for preparing the metal-coated hollow glass microspheres includes the following steps:
[0074] Hollow glass microspheres of soda lime borosilicate, which had been acid-washed with nitric acid and alkaline-washed with sodium carbonate, were immersed in an electrolyte for electroplating treatment at a current density of 2.4 A / dm³. 2 Electroplated glass microspheres were obtained; the obtained electroplated glass microspheres were passivated at 70°C for 30 min using a mixed aqueous solution of nitric acid and sodium dichromate, wherein the mass concentration of nitric acid in the mixed aqueous solution was 30% and the mass concentration of sodium dichromate was 2%, thus obtaining the metal-coated hollow glass microspheres.
[0075] The electrolyte comprises, by weight fraction: 15 parts stannous sulfate, 15 parts zinc sulfate, 40 parts citric acid, 10 parts tartaric acid, 15 parts ammonium chloride, 15 parts ammonia, 15 parts glycolic acid, and 10 parts sodium dodecyl sulfate.
[0076] Example 4
[0077] This embodiment provides a metal-coated hollow glass microsphere, which differs from Embodiment 1 in that the thickness of the tin-zinc alloy coating is adjusted to 8 μm, resulting in a density of 1.6 g / cm³ for the metal-coated hollow glass microsphere. 3 Everything else is the same as in Example 1.
[0078] Example 5
[0079] This embodiment provides a metal-coated hollow glass microsphere, which differs from Embodiment 1 in that the thickness of the tin-zinc alloy coating is adjusted to 22 μm, resulting in a density of 2.1 g / cm³ for the metal-coated hollow glass microsphere. 3 Everything else is the same as in Example 1.
[0080] Example 6
[0081] This embodiment provides a metal-coated hollow glass microsphere. The preparation method of the metal-coated hollow glass microsphere differs from that of Embodiment 1 in that tartaric acid and ammonium sulfate are not added to the electrolyte, while the rest are the same as in Embodiment 1.
[0082] Example 7
[0083] This embodiment provides a metal-coated hollow glass microsphere. The preparation method of the metal-coated hollow glass microsphere differs from that of Embodiment 1 in that malic acid is not added to the electrolyte, while the rest is the same as in Embodiment 1.
[0084] Comparative Example 1
[0085] This comparative example provides a metal-coated hollow glass microsphere, which differs from Example 1 in that the density of the soda lime borosilicate hollow glass microsphere and the tin-zinc alloy coating is adjusted so that the density of the metal-coated hollow glass microsphere is 1.3 g / cm³. 3 Everything else is the same as in Example 1.
[0086] Comparative Example 2
[0087] This comparative example provides a metal-coated hollow glass microsphere, which differs from Example 1 in that the density of the soda lime borosilicate hollow glass microsphere and the tin-zinc alloy coating is adjusted so that the density of the metal-coated hollow glass microsphere is 2.5 g / cm³. 3 Everything else is the same as in Example 1.
[0088] Comparative Example 3
[0089] This comparative example provides a hollow glass microsphere, which differs from Example 1 in that the surface of the soda lime borosilicate hollow glass microsphere is not coated with a tin-zinc alloy coating, but otherwise it is the same as Example 1.
[0090] Comparative Example 4
[0091] This comparative example provides a metal-coated hollow glass microsphere. The preparation method of the metal-coated hollow glass microsphere differs from that of Example 1 in that the electroplated glass microsphere is not passivated, while the rest is the same as that of Example 1.
[0092] The mechanical properties of the metal-coated hollow glass microspheres provided in Examples 1-7, Comparative Examples 1, 2, and 4, and the hollow glass microspheres provided in Comparative Example 3 were tested, and the results are shown in Table 1.
[0093] Table 1
[0094]
[0095] As can be seen from Table 1, the metal-coated hollow glass microspheres provided by the present invention have excellent mechanical properties and their density matches that of cementing slurry, thereby ensuring cementing quality.
[0096] A comparison of Examples 1 with Examples 4 and 5 shows that if the thickness of the tin-zinc alloy coating is too low, the compressive strength that the glass microspheres can withstand will decrease, while the elongation at break will increase, making it difficult for the metal-coated hollow glass microspheres to provide effective rigidity. If the thickness is too high, the compressive strength will increase significantly, but the elongation at break will decrease, resulting in high brittleness of the metal-coated hollow glass, which is prone to premature fracture before experiencing fracture slip, leading to stress concentration. A comparison of Examples 1 with Examples 6 and 7 shows that if no auxiliary complexing agent is added to the electrolyte used for electroplating, the coating will not be able to effectively cover the microspheres, making them no different from ordinary hollow microspheres in performance. If no stabilizer is added, the coating thickness will be uneven, and the mechanical strength will exhibit anisotropy.
[0097] As can be seen from the comparison between Example 1 and Comparative Examples 1 and 2, the density of the metal-coated hollow glass microspheres is too small or too large, which cannot match the density of the cementing slurry, thus reducing the cementing quality. As can be seen from the comparison between Example 1 and Comparative Example 3, the hollow glass microspheres without a tin-zinc alloy coating will have a significantly reduced density, which will reduce the cementing quality when added to the cement slurry as an additive. As can be seen from the comparison between Example 1 and Comparative Example 4, the electroplated glass microspheres without passivation treatment will reduce the wear resistance of the tin-zinc alloy coating.
[0098] In summary, the metal-coated hollow glass microspheres provided by this invention combine hollow glass microspheres with a tin-zinc alloy coating to form a composite structure of a lightweight core and a high-density coating. During fracturing, the fracture is activated by the fracturing fluid and then slides, breaking up the cement stone and the metal-coated hollow glass microspheres. The broken metal-coated hollow glass microspheres provide space for formation slippage, thereby reducing casing deformation. In addition, the outer tin-zinc alloy coating increases the overall density of the hollow glass microspheres to 1.6-2.1 g / cm³. 3Its density far exceeds that of conventional hollow microspheres, compared to the density of conventional well cement slurry (1.8-2.1 g / cm³). 3 The perfect match solves the problem of reduced cementing quality caused by the low density of traditional hollow microspheres. The metal-coated hollow glass microspheres provided by this invention also possess excellent mechanical properties and corrosion resistance, meeting the application requirements in extreme environments.
[0099] The method for preparing metal-coated hollow glass microspheres provided by this invention involves electroplating with an electrolyte of a specific formulation. The electrolyte contains metal ions, which are reduced to metal and deposited on the hollow glass microspheres by the action of an electric current, forming a metal coating on the surface. Passivation treatment of the electroplated glass microspheres can ensure the corrosion resistance, sulfur resistance, compressive strength, and ductility of the metal coating under high temperature and high pressure well conditions.
[0100] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A type of metal-coated hollow glass microsphere, characterized in that, The metal-coated hollow glass microspheres comprise soda lime borosilicate hollow glass microspheres and a tin-zinc alloy coating on their surface; the density of the metal-coated hollow glass microspheres is 1.6-2.1 g / cm³. 3 .
2. The metal-coated hollow glass microspheres according to claim 1, characterized in that, The diameter range of the soda lime borosilicate hollow glass microspheres is 100-250 μm.
3. The metal-coated hollow glass microspheres according to claim 1, characterized in that, The wall thickness of the soda lime borosilicate hollow glass microspheres is 1-2 μm.
4. The metal-coated hollow glass microspheres according to claim 1, characterized in that, The density of the soda lime borosilicate hollow glass microspheres is 0.12-0.8 g / cm³. 3 .
5. The metal-coated hollow glass microspheres according to claim 1, characterized in that, The density of the tin-zinc alloy coating is 7.1-7.5 g / cm³. 3 .
6. The metal-coated hollow glass microspheres according to claim 1, characterized in that, The thickness of the tin-zinc alloy coating is 10-20 μm.
7. A method for preparing metal-coated hollow glass microspheres as described in any one of claims 1-6, characterized in that, The preparation method includes the following steps: Surface-treated soda lime borosilicate hollow glass microspheres are immersed in an electrolyte for electroplating to obtain electroplated glass microspheres; the obtained electroplated glass microspheres are then passivated to obtain the metal-coated hollow glass microspheres.
8. The preparation method according to claim 7, characterized in that, The surface treatment includes acid washing and / or alkaline washing.
9. The preparation method according to claim 8, characterized in that, The reagents used for pickling include hydrochloric acid and / or nitric acid.
10. The preparation method according to claim 8, characterized in that, The reagents used for alkaline washing include sodium hydroxide and / or sodium carbonate.
11. The preparation method according to claim 7, characterized in that, The electrolyte comprises, by weight, 10-15 parts stannous sulfate, 10-15 parts zinc sulfate, 35-40 parts main complexing agent, 20-25 parts auxiliary complexing agent, 10-15 parts pH adjuster, 10-15 parts stabilizer, and 5-10 parts brightener.
12. The preparation method according to claim 11, characterized in that, The primary complexing agent includes citric acid.
13. The preparation method according to claim 11, characterized in that, The auxiliary complexing agent comprises: 5-10 parts tartaric acid and 15-20 parts ammonium salt.
14. The preparation method according to claim 13, characterized in that, The ammonium salt includes at least one of ammonium sulfate, ammonium nitrate, or ammonium chloride.
15. The preparation method according to claim 11, characterized in that, The pH adjuster includes ammonia.
16. The preparation method according to claim 11, characterized in that, The stabilizer includes any one of malic acid, glycolic acid, lactic acid, or glycolic acid.
17. The preparation method according to claim 11, characterized in that, The brightener includes at least one of sodium dodecyl sulfate, formaldehyde, or o-toluidine condensate.
18. The preparation method according to claim 7, characterized in that, The current density for the electroplating process is 1-2.4 A / dm. 2 .
19. The preparation method according to claim 7, characterized in that, The passivating agent used in the passivation treatment includes a mixed aqueous solution of nitric acid and sodium dichromate, wherein the mass concentration of nitric acid is 20-30% and the mass concentration of sodium dichromate is 1-2%.
20. The preparation method according to claim 7, characterized in that, The passivation treatment is performed at a temperature of 50-70℃ for 30-90 minutes.
21. An application of the metal-coated hollow glass microspheres as described in any one of claims 1-6, characterized in that, The metal-coated hollow glass microspheres are used as an additive for preventing the cement slurry from turning into a mold.
Citation Information
Patent Citations
Cement paste for inhibiting deformation of casing and preparation method thereof
CN115286306A
Well cementation tool for enhancing shearing performance of casing pipe at stratum slippage section
CN214464059U
Chemical plating Ni-P alloy technology of glass micro beads
CN102010136A
Process for producing hollow micro bead / aluminium based composite material
CN1339417A